Erosion levels and comparison of erosion estimation methods in watersheds: Disaster risk assessment and environmental engineering approaches - Fahmi, Faizal Nur (Calamity: A Journal of Disaster Technology and Engineering, 2025)
Background: The Blongkeng Watershed is part of the Progo Watershed, located on the north-western slopes of Mount Merapi. The damage to vegetation and land degradation due to volcanic activity from Mount Merapi has led to surface runoff and erosion on the western slopes of the mountain. The aim of this study is to compare the erosion estimation models of morphometry and USLE. Methods: Morphometric parameters were obtained from the River Network Map and Digital Elevation Model (DEM) map, then analyzed quantitatively, and rankings were applied to determine the erosion sensitivity ranking within the watershed. The USLE erosion values were derived from factors affecting erosion, including rainfall erosivity, soil erodibility, slope, and land cover factors. Findings: The erosion levels in the Blongkeng Watershed, calculated using the USLE method, show high values in the upper Sub-Watersheds, ranging from 7.21 to 5.94 tons/ha/year. The comparison between the morphometric and USLE erosion estimation methods yields rankings of erosion levels in the Blongkeng Watershed. The rankings are the same in the upper part of the Blongkeng Watershed, while differences in rankings appear in the middle and lower regions. Conclusion: These differences are likely due to the different input data of the two erosion estimation models and the inclusion of morphometric parameters that may not be suitable for the Blongkeng Watershed ranking calculation. The similarity in rankings in the upper regions is likely due to the area being dominated by slopes greater than 8%. Novelty/Originality of this article: The novelty of this research lies in offering a measurement and comparison of erosion levels.